Describing Patterns of Known Domestic Abuse Among Different Ethnic Groups - Bland, Matthew; Weir, Ruth; Adisa, Olumide; Allen, Katherine; Ferreira, Joana; Maitra, Dev Rup (Frontiers in Psychology, 2022)
Domestic abuse perpetration remains a major threat to public health, safety and wellbeing, causing serious harms and contributing significantly to overall crime globally. In the United Kingdom, research links the crime type to high economic and social costs. In the last 10 years, our collective knowledge of domestic abuse has grown in conjunction with its prioritisation in government policy. Several innovative studies have built a picture of the most serious cases and overall patterns of abuse but to date, examination of these trends by ethnic groups has been limited despite increasing attention to disproportionality in racially minoritised communities in criminal justice system outcomes. In this article we aimed to address this issue through the analysis of 150,000 domestic abuse records kept by police forces in England. Using descriptive statistics, we examined the relative distributions of different ethnicities by suspected offending rate, investigative outcome and crime harm. We found two patterns of note: firstly, that suspects from several categories of minoritized communities are consistently over-represented compared to the White British population among most harmful cases, and secondly, that in Asian communities, offences are less frequently “solved.” We discuss the implications for future research and practice.